DAMPAK KOMUNIKASI TERHADAP KINERJA SUMBER DAYA MANUSIA MELALUI DISIPLIN DAN KEPUASAN KERJA PADA DINAS PERTANIAN DAN PETERNAKAN PROVINSI SULAWESI TENGGARA - Titin Prihatin (Jurnal Riset Bisnis Indonesia, 2015)
This study aims to determine the impact of communicationon the performance of human resourcesthrough discipline and job satisfaction in the department of agriculture and animal husbandry inSoutheast Sulawesi by using asample of 98employees. Technical analysis is the PLS (PartialLeast Square). The results of this study showed a significant positive effect of communicationonjob satisfaction, work discipline, and performance of human resources, as well as a significantpositive effect of job satisfaction on work discipline. While job satisfaction and work discipline haveno significant effects on the performance of human resources. The implication of this study is toimprove job satisfaction, work discipline and the need to pay attention to employee performance andestablish communication to create an atmosphere conducive to work.Keywords: communication, job satisfaction, work discipline, and human resource performance